2020
DOI: 10.1002/alz.12107
|View full text |Cite
|
Sign up to set email alerts
|

Salivary lactoferrin as biomarker for Alzheimer's disease: Brain‐immunity interactions

Abstract: Objective We aim to explain why salivary lactoferrin (Lf) levels are reduced in patients suffering mild cognitive impairment (MCI) and sporadic Alzheimer's disease (sAD).1 We also will discuss if such Lf decrease could be due to a downregulation of the sAD associated systemic immunity. Background Several non‐neurological alterations have been described in sAD, mainly in skin, blood cell, and immunological capacities. We reviewed briefly the main pathophysiological theories of sAD (amyloid cascade, tau, unfolde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 48 publications
4
27
0
Order By: Relevance
“…In this vein, previous studies have shown an association between periodontal disease and brain Aβ accumulation in normal aging, suggesting that periodontal inflammation/infection may accelerate brain Aβ deposition [ 63 , 64 ]. Our results complement these findings, suggesting that reductions of sLF relate to increased regional Aβ burden, which may reflect early immunological alterations potentially associated with higher risk of developing AD [ 60 ]. Alternatively, a recent study has shown that levels of LF in either saliva or cerebrospinal fluid (CSF) were not able to differentiate between controls, MCI/AD, and non-AD dementias.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In this vein, previous studies have shown an association between periodontal disease and brain Aβ accumulation in normal aging, suggesting that periodontal inflammation/infection may accelerate brain Aβ deposition [ 63 , 64 ]. Our results complement these findings, suggesting that reductions of sLF relate to increased regional Aβ burden, which may reflect early immunological alterations potentially associated with higher risk of developing AD [ 60 ]. Alternatively, a recent study has shown that levels of LF in either saliva or cerebrospinal fluid (CSF) were not able to differentiate between controls, MCI/AD, and non-AD dementias.…”
Section: Discussionsupporting
confidence: 82%
“…In consonance with previous results obtained in MCI and AD patients [ 29 , 30 ], decreased levels of sLF were related to increased Aβ burden in left parieto-temporal regions of cognitively normal older adults. We have recently hypothesized that reduced sLF observed in prodromal and clinical stages of AD may indicate early immunological disturbances that eventually increase the risk of AD [ 60 ]. Low levels of sLF may assist oral dysbiosis, which, in turn, may produce long-term infections and a pro-inflammatory response that weakens the blood brain barrier, facilitating colonization of brain tissue by periodontal bacteria [ 61 ] and accelerating neuroinflammation that contribute to AD pathology [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Reduced Lf levels can be used to identify subjects with positive cerebral amyloidosis [99], and this finding is consistent with a previous study [100]. Bermejo-Pareja et al hypothesized that the reduced levels of salivary (Lf) may be related to immunological disturbances in AD, and this observation agrees with the physiopathological explanations of AD [101]. In a pilot study, a targeted and quantitative metabolomics approach is applied, and several panels composed of urinary metabolites are identified to distinguish MCI and AD from cognitively healthy controls with high sensitivity and specificity [102].…”
Section: Biomarkers In the Urine And Salivasupporting
confidence: 87%
“…This approach opened the way for a paradigm shift in studying a new “infection hypothesis,” or perhaps more broadly, “innate immune system dysregulation hypothesis”. It suggests the role of chronic infections in the development of AD, as well as a potential deregulation of the human innate immune response to these infections, as a plausible route for new investigations of the aetiology and pathophysiology of AD [43] . Although AD is a complex disease and microbial infection may not be the sole cause, this new paradigm may provide novel targets for the prevention and treatment of this devastating disease.…”
Section: Discussionmentioning
confidence: 99%